PENINGKATAN KUALITAS INFRASTRUKTUR JALAN PADA TANAH EKSPANSIF DENGAN PEMANFAATAN LIMBAH PERTANIAN GUNA MENDUKUNG PENGEMBANGAN WILAYAH - G D. Pandulu; Suhudi Suhudi (Universitas Tribhuwana Tunggadewi, 2012)
Soil with high variability of shrinkage is one of contributed factor on main constraints in road contruction Probolinggo region is one of the areas has those problem of road contruction , and to overcome the problem by using soil amandement as soil stability. The aims of this study was to determine soil in Probolinggo as shrinkage soil types or not by application of ash rice husk. Result showed that by soil physical determination soil strength 2.233 g/m3, water content 50,15%, wet bulk soil 1,61 g/m3, dry bulk 1,15 kN/m3, Liqiut Limit (LL) 86,5%, Plastic limit (PL) 39,8% and Plasticity limit (PI) 47,1%. In general high plasticity value of soil will be showed highly soil shrinkage. Ash of rice husk with containt of SiO2 90% can be used as soil stability, and to reduce value of plasticity limit to 37,68% is needed about 10% ash rice husk. For main body road of 1 km is needed 669 ton of ash rice husk from burning rice husk 3.345 ton , and rice husk from about 16.725 dry rice milling